2010
DOI: 10.1523/jneurosci.2557-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Active TRPV1 Tonically Drives Central Spontaneous Glutamate Release

Abstract: Central synapses spontaneously release neurotransmitter at low rates. In the brainstem, cranial visceral afferent terminals in caudal solitary tract nucleus (NTS) display pronounced, activity-dependent, asynchronous release of glutamate and this extra release depends on TRPV1 receptors (TRPV1ϩ). Asynchronous release is absent for afferents lacking TRPV1 (TRPV1Ϫ) and resting EPSC frequency was greater in TRPV1ϩ. Here, we studied this basal activity difference by assessing thermal sensitivity of spontaneous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 33 publications
5
118
0
Order By: Relevance
“…5D). This proximity suggested that CAP sensitivity may correlate with thermal sensitivity as previously observed in NTS (Shoudai et al 2010). Although the majority of Vc neurons (67%, n ϭ 36 of 54; Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…5D). This proximity suggested that CAP sensitivity may correlate with thermal sensitivity as previously observed in NTS (Shoudai et al 2010). Although the majority of Vc neurons (67%, n ϭ 36 of 54; Fig.…”
Section: Resultssupporting
confidence: 81%
“…However, at central synapses measured in slices, neurotransmitter release occurs spontaneously, and such events are commonly viewed as arising from infrequent and stochastic release from the same pools of vesicles as action potential-evoked release (Ermolyuk et al 2013;Katz 1971). In contrast to peripheral activation characteristics, the rates of spontaneous vesicle release are often much higher from primary afferent terminals (Grudt and Williams 1994;Shoudai et al 2010;Uta et al 2010). Indeed, primary afferents that contact second-order neurons in the solitary tract nucleus (NTS) often express the transient receptor potential (TRP) vanilloid type 1 channel (TRPV1) and have substantially higher spontaneous glutamate release rates than neurons with afferents lacking TRPV1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in animals show that these channels are involved in the regulation of synaptic transmission in peripheral (Caterina et al, 1997;Sikand and Premkumar, 2007) and central (Gibson et al, 2008;Peters et al, 2010;Shoudai et al, 2010) structures, by enhancing glutamate release from nerve endings. Accordingly, physiological studies have shown that stimulation of TRPV1 channels with capsaicin or anandamide enhances the frequency of glutamate-mediated spontaneous and miniature EPSCs, whereas GABAergic synaptic transmission is unaffected (Yang et al, 1998;Marinelli et al, 2002Marinelli et al, , 2003Li et al, 2004;Derbenev et al, 2006;Starowicz et al, 2007;Xing and Li, 2007;Musella et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, physiological studies have shown that stimulation of TRPV1 channels with capsaicin or anandamide enhances the frequency of glutamate-mediated spontaneous and miniature EPSCs, whereas GABAergic synaptic transmission is unaffected (Yang et al, 1998;Marinelli et al, 2002Marinelli et al, , 2003Li et al, 2004;Derbenev et al, 2006;Starowicz et al, 2007;Xing and Li, 2007;Musella et al, 2009). Recent studies also show that the regulation of spontaneous glutamate release by TRPV1 receptors is activity dependent Shoudai et al, 2010), because afferent activation triggers long-lasting asynchronous glutamate release only from synapses expressing the TRPV1 receptor, strongly potentiating the duration of postsynaptic spiking . TRPV1 has also been involved in the regulation of synaptic plasticity and in particular in hippocampal long-term potentiation (LTP) (Marsch et al, 2007) and depression (LTD) (Gibson et al, 2008) and also in hippocampus-dependent learning in mice (Marsch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%